(untitled) (Revista Educação, Artes e Inclusão, 2025)
This research addresses a teacher training process in which Heritage Education stands out. It is an artistic inquiry developed at the University of Bologna (Italy), where both students and university teachers participate. It proposes an artistic approach to the cemeteries of northern Italy, as an important heritage entity, reflecting on the power that themes such as death or cemeteries exercise in our cultural background. There are unusual themes. We emphasize their presence as a collective imagination to carry out an artistic action, which finally materializes with an exhibition at the Galleria Studio Cenacchi in Bologna. The exhibition incorporates photography from students. For several weeks the exhibition was complemented with guided tours. We developed our research based on the case study methodology, incorporating Art-Based Research. The exhibition generates debates and reflections, using the charismatic figure of Pier Paolo Pasolini as the element of the proposal. Participatory action serves to motivate students, with their photos and comments. This model of innovative and original creations proposes a type of teaching practice in art education that focuses on rarely topics in the curriculum, incorporating problems of a social, political and cultural nature. We investigate from art and from teaching practice itself, involving university students in innovative models.